INTONATION MEANING IN ENGLISH DISCOURSE: A STUDY OF THAI SPEAKERS - Budsaba Kanoksilapatham (Universitas Katolik Indonesia Atma Jaya, 2005)
At the heart of cross-cultural misunderstandings lie problems associated with intonation features of learners of English (Gumperz et al., 1979; Gumperz, 1982). The successful use of discourse intonation contributes to effective cross-cultural communication, and failure to make use of the appropriate pragmatic discourse features of English intonation jeopardizes effective communication, possibly resulting in serious communication breakdown between native and non-native speakers. Despite its crucial role in communication and language learning, many English language learners have difficulty in using appropriate intonation. A number of studies of second language intonation have an underlying assumption of the role of cross-linguistic interference contributing to a “foreign intonation” (Lepetit, 1989; Hewings, 1990; Wennerstrom, 1994). However, this line of research is in an early stage and the findings are as yet inconclusive. This paper compared the speech of five Thai speakers who were studying for their advanced degrees in science and business in the U.S with the speech produced by five native speakers. The speech elicited from three different tasks was analyzed using Pierrehumbert & Hirschberg’s 1990 model of intonational meaning. The extent to which the intonation produced by Thais diverged from that by native speakers was assessed. In light of the findings, pedagogical suggestions were offered to help improve the teaching of pronunciation, in general, and the teaching of intonation, in particular. Keywords: discourse intonation, cross-cultural communication,cross-linguistics interference